2016
DOI: 10.1038/srep33569
|View full text |Cite
|
Sign up to set email alerts
|

CXCL13, CXCL10 and CXCL8 as Potential Biomarkers for the Diagnosis of Neurosyphilis Patients

Abstract: At present, diagnosis for neurosyphilis remains a major clinical challenge. Venereal Disease Research Laboratory (VDRL) titer of the cerebrospinal fluid (CSF) is suboptimally sensitive to diagnose neurosyphilis, which can be negative in neurosyphilis patients, especially in asymptomatic neurosyphilis patients. In the search for biomarkers of neurosyphilis, we investigated the chemokine profile in CSF of neurosyphilis patients and found that the concentrations of CXCL13, CXCL10 and CXCL8 were selectively elevat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
46
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 25 publications
6
46
1
Order By: Relevance
“…A combination of three chemokines was positively correlated to a high AUC value (0.949), 90.4% sensitivity, and 92.9% specificity. However, it was not markedly different from the high diagnostic significance of CXCL13 or VDRL [55]. Therefore, CXCL13 may be a good diagnostic marker in situations in which CSF-VDRL results are nonreactive [53].…”
Section: Cxcl13 Concentrationmentioning
confidence: 74%
See 2 more Smart Citations
“…A combination of three chemokines was positively correlated to a high AUC value (0.949), 90.4% sensitivity, and 92.9% specificity. However, it was not markedly different from the high diagnostic significance of CXCL13 or VDRL [55]. Therefore, CXCL13 may be a good diagnostic marker in situations in which CSF-VDRL results are nonreactive [53].…”
Section: Cxcl13 Concentrationmentioning
confidence: 74%
“…The cut-off point of Q CXCL13 indicated by the authors showed 87.5% sensitivity and 69.2% specificity, which may suggest that Q CXCL13 is a good diagnostic marker to discriminate neurosyphilis from syphilis and other neurological diseases [11]. Furthermore, some studies have demonstrated that the CSF/serum ratio is significantly increased in neurosyphilis patients [12,55]. Rupprecht et al observed that in 100% of neurosyphilis patients the ratio was low (below 4), whereas in 89.5% of neuroborreliosis patients, the ratio was above the cut-off value.…”
Section: Cxcl13 Concentrationmentioning
confidence: 78%
See 1 more Smart Citation
“…While these techniques, and others, appear to improve the sensitivity of existing CSF serology they are considerably more labour intensive than existing techniques and are yet to be validated or widely applied. CSF cytokine and chemokine profiling of patients with neurosyphilis has led to an expanding library of novel markers that correlate with CNS inflammatory responses and invasion of the CNS . A prospective study looking at the utility of CSF levels of chemokine CXCL 13 and T. pallidum DNA PCR to improve diagnostic accuracy in patients with suspected neurosyphilis has recently begun recruiting in Shanghai (Clinical Trials Registry number ChiCTR‐DDD‐16009591).…”
mentioning
confidence: 99%
“…CSF cytokine and chemokine profiling of patients with neurosyphilis has led to an expanding library of novel markers that correlate with CNS inflammatory responses and invasion of the CNS. [18][19][20] A prospective study looking at the utility of CSF levels of chemokine CXCL 13 and T. pallidum DNA PCR to improve diagnostic accuracy in patients with suspected neurosyphilis has recently begun recruiting in Shanghai (Clinical Trials Registry number ChiCTR-DDD-16009591). Validation of these indicators will be difficult and further work is required before these tests can be confidently incorporated into any existing neurosyphilis diagnostic algorithm.…”
mentioning
confidence: 99%